Economic and environmental comparative analysis on macro-femtocell deployments in LTE-A - Vaz. F.; Sebastião, P.; Gonçalves, L.; Correia, A. (Wireless VITAE 2013, 2013)
This paper describes the economic and environmental comparative analysis performed on macro and femtocell deployments and most prevalent results obtained. Four specific scenarios are studied and, for each one, an evaluation is made in terms of capacity, cost effectiveness and expected carbon emissions. It provides mobile networks operators (MNO) with relevant information, enabling them to adapt business models and deployment approaches to current and future trends in a sustainable way, while minimizing capital (CAPEX) and operation expenses (OPEX).